Suicide Intervention Gatekeeper Training: Modeling Mediated Effects on Development and Use of Gatekeeper Behaviors. (October 2018) - Osteen, Philip J.
Objective: Suicide is a significant public and mental health crisis in the United States. Training providers in suicide assessment and response is designated as one of the primary strategies for reducing deaths by suicide. Research has established that suicide intervention training is effective, but little work has been published on potential mediators of skill development and use. Method: Secondary data analysis of a randomized trial of the Question, Persuade, and Refer gatekeeper training with master of social work students. Path analysis was used to estimate mediated effects of knowledge, attitudes, reluctance, and self-efficacy on behavior outcomes. Results: Results suggest improvements in posttraining measures for knowledge, attitudes, self-efficacy, reluctance, and the use of gatekeeper behaviors, but there was no supporting evidence for the presence of mediated effects on behavior. Only self-efficacy demonstrated a strong direct relationship with gatekeeper behaviors. Conclusions: Ongoing evaluation is needed with an added interest in self-efficacy and how it can be enhanced through training.